Acidosis Maintains the Function of Brain Mitochondria in Hypoxia-Tolerant Triplefin Fish: A Strategy to Survive Acute Hypoxic Exposure? - Devaux, Jules B. L.; Hedges, Christopher P.; Birch, Nigel; Herbert, Neill; Renshaw, Gillian M. C.; Hickey, Anthony J. R. (Frontiers in Physiology, 2019)
The vertebrate brain is generally very sensitive to acidosis, so a hypoxia-induced decrease in pH is likely to have an effect on brain mitochondria (mt). Mitochondrial respiration (JO2) is required to generate an electrical gradient (∆Ym) and a pH gradient to power ATP synthesis, yet the impact of pH modulation on brain mt function remains largely unexplored. As intertidal fishes within rock pools routinely experience hypoxia and reoxygenation, they would most likely experience changes in cellular pH. We hence compared four New Zealand triplefin fish species ranging from intertidal hypoxia-tolerant species (HTS) to subtidal hypoxia-sensitive species (HSS). We predicted that HTS would tolerate acidosis better than HSS in terms of sustaining mt structure and function. Using respirometers coupled to fluorimeters and pH electrodes, we titrated lactic-acid to decrease the pH of the media, and simultaneously recorded JO2, ∆Ym and H+ buffering capacities within permeabilized brain and swelling of mt isolated from non-permeabilised brains. We then measured ATP synthesis rates in the most HTS (Bellapiscus medius) and the HSS (Forsterygion varium) at pH 7.25 and 6.65. Mitochondria from HTS brain did have greater H+ buffering capacities than HSS mt (~10 mU pH.mgprotein-1). HTS mt swelled by 40% when exposed to a decrease of 1.5 pH units, and JO2 was depressed by up to 15% in HTS. However, HTS were able to maintain ∆Ym near -120 mV. Estimates of work, in terms of charges moved across the mt inner-membrane, suggested that with acidosis, HTS mt may in part harness extra-mt H+ to maintain ∆Ym, and could therefore support ATP production. This was confirmed with elevated ATP synthesis rates and enhanced P:O ratios at pH 6.65 relative to pH 7.25. In contrast, mt volumes and ∆Ym decreased downward pH 6.9 in HSS mt and paradoxically, JO2 increased (~25%) but ATP synthesis and P:O ratios were depressed at pH 6.65. This indicates a loss of coupling in the HSS with acidosis. Overall, the mt of these intertidal fish have adaptations that enhance ATP synthesis efficiency under acidic conditions such as those that occur in hypoxic or reoxygenated brain.